Relationship between macronutrient intake and physical activity with fitness on employees in Pandeglang Hospital - Silvia Dwi Rahmawati (ARGIPA (Arsip Gizi dan Pangan), 2019)
ABSTRACT Physical fitness is the ability of one's body to do daily work without causing significant fatigue. Several factors related to fitness are nutritional status, level of physical activity, intake of macro nutrients, genetic makeup, age, sex, health status. The purpose of this study was to analyze the relationship between the level of energy sufficiency and macro nutrients, the level of physical activity with the level of fitness in Pandeglang District Hospital employees. The study design was cross sectional with 75 respondents and used a chi-square analysis test. There is no relationship between the level of energy sufficiency (p-value 1,000) the level of protein sufficiency (p-value 1,000), the level of fat sufficiency (p-value 1,000), the level of carbohydrate adequacy (p-value 0.768) with the fitness level of employees of Pandeglang District Hospital. There is a relationship between physical activity (p-value 0,000) with the fitness level of employees of Pandeglang District Hospital. Employees who have a sufficient level of energy and macro nutrients are on average have a less fitness level. Employees who have a mild level of physical activity tend to have less fitness. So it is necessary to monitor food intake, and the level of physical activity on employees. Keywords: Macro Nutrition Intake, Physical Activity, Fitness Level